Carbon-Based Catalyst Synthesized and Immobilized under Calcium Salt Assistance To Boost Singlet Oxygen Evolution for Pollutant Degradation - Huang, Bao-Cheng; Huang, Gui-Xiang; Jiang, Jun; Liu, Wu-Jun; Yu, Han-Qing (ACS applied materials & interfaces, 2019)
Carbon-based materials are recognized as promising candidates for pollutant degradation because of their environmental benignity. Massive and cost-effective production and efficient recovery of carbon-based catalysts are crucial to apply this technology. However, various nanostructured carbons with different dimensions are usually utilized as precursors while not considering their complex preparation procedures and the high costs of ingredients. Moreover, catalyst separation and recovery are not given sufficient attention. In this work, a calcium salt-assisted pyrolysis strategy is proposed to tune the catalytic site formation of carbon-based catalysts. Results show that blending equal amounts of Ca2+ (calcium chloride) and organic precursors could greatly improve the catalytic activity of the carbonated product to activate peroxymonosulfate for pollutant degradation. In addition, the proposed synthetic strategy is universal to most of the readily accessed and cost-effective organic precursors. Singlet oxygen is identified as the main reactive oxidant for pollutant removal in the catalytic reaction. By cross-linking calcium ions and alginate as a hydrogel to immobilize the catalyst, the carbon material could be readily recovered. Furthermore, a long-term continuous-flow reactor test is conducted to validate the effectiveness of applying the immobilized catalyst to treat a synthetic wastewater with 0.5 mM bisphenol A. As a result, a green synthesis and immobilization strategy for persulfate catalysts is successfully established, and the prepared catalyst might be applied for wastewater treatment through using calcium salt in two purposes.